2014
DOI: 10.1063/1.4901437
|View full text |Cite
|
Sign up to set email alerts
|

Far field emission profile of pure wurtzite InP nanowires

Abstract: We report on the far field emission profile of pure wurtzite InP nanowires in comparison to InP nanowires with predominantly zincblende crystal structure. The emission profile is measured on individual nanowires using Fourier microscopy. The most intense photoluminescence of wurtzite nanowires is collected at small angles with respect to the nanowire growth axis. In contrast, zincblende nanowires present a minimum of the collected light intensity in the direction of the nanowire growth. Results are explained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…To quantify the absorption and emission between the components and to calculate the corresponding coupling weight matrix g ij , a full 3D model of the optical network with its node components was implemented in a Finite Difference Time Domain (FDTD) simulation using the solver from Lumerical . FDTD methods are widely used to model nanowire optical absorption, scattering, and emission, , demonstrating good agreement with experimental observations in nanostructures as used in the present study. In Figure a,b, the field distributions in the attractor ring due to one neural node LED (#3 in Figure a), as well as from an individual component, are seen.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…To quantify the absorption and emission between the components and to calculate the corresponding coupling weight matrix g ij , a full 3D model of the optical network with its node components was implemented in a Finite Difference Time Domain (FDTD) simulation using the solver from Lumerical . FDTD methods are widely used to model nanowire optical absorption, scattering, and emission, , demonstrating good agreement with experimental observations in nanostructures as used in the present study. In Figure a,b, the field distributions in the attractor ring due to one neural node LED (#3 in Figure a), as well as from an individual component, are seen.…”
Section: Resultssupporting
confidence: 72%
“…To simulate the absorption and emission between the components and calculate the corresponding coupling weight matrix 𝑔 𝑖𝑗 , we constructed a full 3D model of the optical network with its node components in the commercially available FDTD solver from Lumerical 36 . FDTD methods are widely used to model nanowire optical absorption 22 , scattering 37 , emission 18,38 , demonstrating good agreement with experimental observations. We determine the absorption of each device by calculating the optical transmission through a closed box around each absorption region in a component.…”
Section: Bottom Right)mentioning
confidence: 66%
“…26 To this day, most of the works done in literature concerning the far-field emission of single QD-NW or NW, is either in the visible or in the near-infrared 900-1000 nm range. 22,[26][27][28][29] However, no study has been reported yet on a single photon emission with a Gaussian far-field radiation in the telecom band from single QD-NWs monolithically grown on Si substrates.…”
mentioning
confidence: 99%
“…As DFT calculations underestimate the band gap significantly, we perform a scissors shift of the conduction band states to the empirically known fundamental gaps of E g = 1.490 eV in wurtzite InP [57] and E g = 0.477 eV in wurtzite InAs [53], respectively. In fact, because the gap in InAs is small, the underestimation of the gap in calculations using the PBE functional leads to the closing of the gap.…”
Section: Band Structure Calculationsmentioning
confidence: 99%